The inhomogeneous Riemanian boundary – value problem with infinite index of the logarithmic order ρj ≥ 1 for complex Dini-Lipshitz contour - Alekna, Petras (Lietuvos matematikos rinkinys, 1999)
Special choosing entire functions, the general solution of the problem in the class of bounded and analytic functions is obtained.